Epidural Anesthesia for Elective Cesarean Section in a Parturient with Noonan Syndrome and Severe Pulmonary Stenosis: A Case Report - Kadek Agus Putra Udayana; I Gusti Ngurah Mahaalit Aribawa; I Ketut Wibawa Nada (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Pregnancy complicated by congenital heart disease (CHD) presents significant anesthetic challenges, particularly in syndromic conditions such as Noonan syndrome characterized by pulmonary stenosis and multiple right-sided valvular abnormalities. We report a 27-year-old primigravida at 37+5 weeks of gestation with a clinical suspicion of Noonan syndrome, severe pulmonary stenosis, tricuspid and pulmonary valve regurgitation, and right heart failure classified as New York Heart Association (NYHA) class II, who underwent an elective cesarean section combined with intrauterine device (IUD) insertion. An incremental epidural block using 0.5% bupivacaine was selected to provide adequate anesthesia, prevent airway manipulation, and maintain optimal hemodynamic stability under continuous invasive monitoring, including arterial and central venous pressure assessment. The intraoperative and postoperative periods proceeded uneventfully, with stable maternal parameters and a vigorous neonate, both demonstrating favorable recovery and no postoperative complications. This case underscores the importance of an individualized anesthetic approach, meticulous titration of anesthetic agents, and comprehensive perioperative monitoring to ensure safety and positive outcomes in parturients presenting with complex congenital cardiac conditions such as Noonan syndrome.